Lost souls. - Lost Souls; Attitude Records (Kuala Lumpur : Attitude Records, 1999)
Contains twelve rock tracks, bonus track'Everything I Own' (original mix & live mix - extract from Bon Jovi Live Concert at Shah Alam Stadium).
CD 1 : The Happy Crew / (3:59) -- Jessie / (5:10) -- Leaving On A Jet Plane / (4:09) -- The Lost Souls / (4:45) -- 100% / (4:10) -- Malaysia Boleh / (4:20) -- Sarah / (4:13) -- Too Many Promises / (4:24) -- Rainbow I Can Never Find / (4:27) -- Sayu / (4:27) -- Everything I Own (original mix) / (4:30) -- Everything I Own (live mix) / (5:04).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English -- Malaysia